Mid-term functional outcome after distal Achilles tendon rupture anchoring screw repair in elderly osteopenia as a reliable technique: A case report - Teddy Heri Wardhana; Mukhlis Aziz (Universitas Muhammadiyah Surabaya, 2023)
The management of distal Achilles tendon rupture is still controversial, especially in elderly patients, due to poor bone quality and tendon stump integrity. One of the proposed repair techniques is by using an anchoring screw. Here we report the mid-term follow-up of two patients with distal Achilles tendon rupture treated with an anchoring screw. Two elderly males in their sixties came to the outpatient clinic with similar complaints of intermittent pain, reddening, and ankle swelling after falling. Both patients were diagnosed with distal Achilles tendon rupture and were treated with open repair using a Krakow suture and anchoring screws. Functional outcome evaluation postoperatively found a good outcome. Previous studies have shown that repair with the anchoring technique is better biomechanically than with ordinary sutures. Repairs with this technique can withstand greater forces and loads before they fail. An anchoring screw repair technique for total distal Achilles tendon rupture repair provides good results in elderly with osteopenia.